Effects of irrigation-fertilization-aeration coupling on yield and quality of greenhouse tomatoes - Yanan Sun; Linbo Duan; Huayu Zhong; Huanjie Cai; Jiatun Xu; Zhijun Li (Agricultural Water Management, 2024)
Optimal irrigation-fertilization-aeration subsequently enhance greenhouse tomato yields and fruit quality. In addition, the optimization of these agricultural practices is essential to improve irrigation water productivity (WPI). In this context, the present study aims to assess the effects of combined irrigation, fertilization, and aeration treatments on the greenhouse tomato yield (Y), evapotranspiration (ET), WPI, and fruit quality. To achieve this objective, we applied two cumulative pan evaporation (Epan) -based irrigation (I1: 1.0 Epan; I2: 0.8 Epan), three nitrogen fertilization (F1: 120 kg/ha; F2: 180 kg/ha; F3: 240 kg/ha), and three venturi injector-based aeration rates (A1: single Venturi aeration; A2: double Venturi aeration; CK: unaerated) in triplicates. In total, 15 treatment scenarios were considered in this study, including a control group (CKI1). Each treatment was replicated three times. According to the obtained results, the harvesting time of the cultivated greenhouse tomato was strongly affected by the aeration levels due to the differences in the soil oxygen contents. The A2 treatment demonstrated a stronger promoting effect on early tomato ripening than those under the A1 and CK scenarios. Indeed, the first tomato harvest amount under the A2 treatment was higher than those obtained under the A1 and CK scenarios by 32.24% and 36.45% (P < 0.05), respectively. In addition, there were significant increases in the water productivity (WPC) and WPI values with decreasing irrigation rates. In contrast, the ET and Y substantially decreased. Specifically, the ET and Y values under the I1 treatment scenario were 11.38% and 8.65% higher than those observed under the I2 treatment scenario, respectively. On the other hand, the WPC and WPI values under the I1 treatment were 12.01% and 13.09% lower than those under the I2 treatment, respectively. The results showed also significant irrigation-aeration, irrigation-fertilization, and aeration-fertilization interaction effects on the ET, Y, WPC, and WPI values of the greenhouse tomato (P < 0.01). In addition, the irrigation, fertilization, and aeration treatments considerably influenced the sugar-acid ratio and the organic acid, soluble sugar, and lycopene contents in the tomatoes. In fact, lycopene was an important indicator of tomato quality, showing a significant positive correlation with the comprehensive quality scores. Based on the TOPSIS results, the combined I2-F2-A2 treatment is recommended to enhance the Y, ET, WPC, WPI, and fruit quality of the tomato crop.